2011
DOI: 10.1111/j.1476-4431.2011.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous echocardiographic contrast in three dogs

Abstract: SEC is considered a marker for thromboembolic disease in people and can occur in dogs in the absence of significant cardiomegaly. SEC in these 3 dogs may be related to the documented hyperfibrinogenemia. Further investigation is warranted to determine whether dogs with SEC are at an increased risk for thromboembolic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Spontaneous echo contrast has been reported previously in three dogs, secondary to systemic inflammatory conditions (including endocarditis, Evan's syndrome and sepsis) resulting in hyperfibrinogenaemia and platelet activation (Ralph et al . ). Echocardiography was repeated in only one patient, with resolution of the spontaneous echocontrast at 2 weeks but no patients showed signs of cardiac disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Spontaneous echo contrast has been reported previously in three dogs, secondary to systemic inflammatory conditions (including endocarditis, Evan's syndrome and sepsis) resulting in hyperfibrinogenaemia and platelet activation (Ralph et al . ). Echocardiography was repeated in only one patient, with resolution of the spontaneous echocontrast at 2 weeks but no patients showed signs of cardiac disease.…”
Section: Discussionmentioning
confidence: 97%
“…It is thought to be due to changes in blood flow or haematological abnormalities. Reported risk factors for spontaneous echocontrast in dogs and humans include increased fibrinogen levels, red cell distribution width, haematocrit, haemoglobin content, hypercoagulability and platelet size and decreased shear rate (Sigel et al 1983, Ralph et al 2011, Bayar et al 2016. Under normal circumstances, red blood cells are repelled from each other because of their similar electrical charge but macromolecules such as fibrinogen alter and reduce these repulsive forces (Fatkin et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A recent case report of 3 dogs, in contrast, described the development of SEC in the absence of any cardiac disease . SEC in these dogs was assumed to have developed during hypercoagulable states and was resolved once the hypercoagulable states were reversed . Stokol et al.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous echocardiographic contrast in cats appears to be exclusively associated with cardiomyopathy . This is in contrast to a recent case series identifying 3 dogs with SEC, none of whom had cardiac abnormalities on evaluation . A study by Stokol et al evaluated the prevalence of SEC, intracardiac thrombi, and arterial thromboembolism (ATE) in cats, and found that 50% of cardiomyopathic cats with SEC or ATE were hypercoagulable .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation